Legal Protection for the E-Auction System for the Purchase of Pledge Objects at Office Services and State Wealth Auctions (KPKNL) in an Islamic Perspective - Helena Margaret (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2023)
Indonesia is known as a country whose people experience many problems related to debt receivables. However, education regarding collateral rights is still minimal. Therefore , the government provides solutions related to education on the auction of objects through socialization. The purpose of this study discusses the process and protection of legal certainty related to E-Aution of purchasing pawn objects at the KPKNL service seen in its Islamic perspective. This type of research is qualitatively narrative by examining various literature to be discoping into research results. Thereason is, there is socialization related to E-Auction because there is still minimal trust from the E-Auction system. It was seen that there were many cases of irresponsible auctions and plus the majority of Indonesians were Muslims, so the KPKNL office provided progress from collaboration between managers Syar'i-based which is still categorized as new. However, the collaboration process between KPKNL and BSI fosters confidence and trust if the implementation of the E-Auction is in accordance with Minister of Finance Regulation No. 106 / PMK. 06/ 2013 on E-Auction and No. 93/PMK. 06/2010 i.e. preventive protection of auction winners